Building Conditions Assessment of Timber Mosques at Batu Pahat. - Yahya, Nursyahira; Adnan, Nor Azizah (Recent Trends in Civil Engineering and Built Environment, 2025)
This technical study focuses on the evaluation of the structural integrity of timber mosques in Malaysia, specifically Jamek An Nur Kampung Patah Pedang and Kampung Parit Lapis Bangas Mosques in Batu Pahat. A thorough assessment is essential to identify the extent of the problem and develop targeted conservation strategies, ensuring the preservation of cultural heritage. The primary objectives are to evaluate the quality and condition of the timber mosques using a Building Condition Assessment (BCA) checklist and propose recommendations for repairs or replacements based on identified damage. This study employs both primary and secondary data collection methods. Site visits and observations, including crack measurements using crack meters, constitute primary data, while secondary data involves reviewing journals and reports. The severity index is calculated using the formula severity index=frequency (%) x Accumulate multiplier of risk effect. The Australian standard specification 'Timber heavy structural visually’ has been using to check the allowable crack width limit. Condition surveys reveal timber defects in both mosques, with cracks and insect attacks being common issues. Jamek An Nur Kampung Patah Pedang Mosque is assessed as fair, emphasizing the need for addressing identified defects. The highest width of cracks at Jamek An Nur Kampung Patah Pedang Mosque is at the C10 position, measuring 4.3mm, and C21 has a width of 7mm, exceeding the allowable crack line permitted for timber building, which is 3mmIn contrast, Kampung Parit Lapis Bangas Mosque is in good condition, but monitoring, maintenance, and repairs are recommended. Specific remediation strategies are suggested based on the type and severity of observed issues. Regular monitoring, proper ventilation, and timely maintenance are crucial for addressing seasoning and shrinkage cracks. Professional intervention is recommended for wider or deeper splits, while insect or fungal damage requires immediate attention with targeted treatment. Implementing preventive measures through regular inspections contributes to the overall health and longevity of timber buildings.